The silenced voices of architectural discourse: promoting inclusion through qualitative research - Trefry, John H.; Watson, Laurel B. (Enquiry The ARCC Journal for Architectural Research, 2013)
Contemporary architectural discourse is primarily framed by institutional hegemony. Scholarly works written in a voice derived from this privilege inherently exclude the voices of those untrained individuals who inhabit the built environment. The field of architecture, most notably in the AIA's policies and positions, calls for more diverse viewpoints and a more complex understanding of the public's relationship with architecture. It is not possible to make this complexity apparent through the monolithic viewpoints of institutional scholarship. This essay explores a variety of more inclusive research methods established in the social sciences under the banner of qualitative research. We focus on how qualitative research satisfies contemporary research expectations more effectively than positivist institutional scholarship and how qualitative research has a specific congruency with the field of architecture.